Exploring Challenges of Hospital Chaplains in Transdisciplinary Teams - Spates, Stephen A.; Kingsley Westerman, Catherine Y.; Laam, Leslie A.; Goke, Ryan (Frontiers in Communication, 2020)
Hospital chaplains experience obstacles in contributing to team goals and objectives when they are part of transdisciplinary teams. This case study explores the communication challenges of membership on transdisciplinary teams for hospital chaplains. Chaplain David Howard is one of three chaplains at Grace Hospital and is assigned to the newly formed palliative care transdisciplinary team. The purpose of this team is to work towards providing quality care to palliative care patience in the upcoming integrative medicine wing. Although the team is tasked with improving the quality of life for patients, David notices that his concerns of quality of end-of-life care often clash with his medical colleagues’ concerns about improved medical health outcomes.